Implementation of Freight Transport Restriction Policy in Balikpapan City - M Islamiawan; Fajar Apriani; Hariati Hariati (Journal of Government and Politics (JGOP), 2025)
This study analyzes the implementation of the freight transport restriction policy in Balikpapan City by examining the dynamics of operator compliance, institutional coordination, and the policy’s impact on urban mobility and the local economy. Using a qualitative research method with a case study approach, data were collected through in-depth interviews, document analysis, and field observations to understand how the policy functions in practice. The findings reveal that the success of policy implementation depends on the adaptive strategies of freight operators, the effectiveness of institutional coordination, and the suitability of policy design with local urban conditions. While the restriction policies have contributed to reducing congestion and improving urban order, challenges remain in terms of enforcement consistency, resource limitations, and inter-agency collaboration. The study highlights the importance of integrating regulatory control with supportive mechanisms and adaptive governance to achieve sustainable freight transport management in developing urban contexts